Pengaruh Kepuasan Kerja, Motivasi Kerja, dan Lingkungan Kerja terhadap Komitmen Karyawan - Indriyani, Isna; Subiyanto, Didik; Hadi, Syamsul (Fakultas Ekonomi Universitas Samudra, 2024)
This research explores the relationship between job satisfaction, work motivation and work environment on employee commitment. This quantitative research using census techniques involved 43 employees of PT. Alta Danan Jaya Abadi. The hypothesis testing process was carried out using SPSS version 26. The results showed that job satisfaction had a negative and significant effect on employee commitment, but work motivation and work environment had a positive and significant effect on employee commitment. Simultaneously, the three independent variables have a positive and significant effect on employee commitment. The practical implication is that there needs to be reinforcement in increasing salaries, co-workers, and direction from superiors so that employee commitment is maintained.